2021
DOI: 10.3390/microorganisms9050969
|View full text |Cite
|
Sign up to set email alerts
|

Limonin Enhances the Antifungal Activity of Eugenol Nanoemulsion against Penicillium Italicum In Vitro and In Vivo Tests

Abstract: Penicillium italicum, the cause of citrus blue mold, is a pathogenic fungus that seriously affects the postharvest quality of citrus fruit and causes serious economic loss. In this study, a eugenol nanoemulsion containing limonin, an antimicrobial component from citrus seeds, was prepared using a high-pressure microfluidizer and the antifungal activity of the nanoemulsions against P. italicum was evaluated based on the conidial germination rate, mycelial growth, and scanning electron microscopy analysis. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 47 publications
(55 reference statements)
1
5
0
Order By: Relevance
“…The diameter of the zones of inhibition of EuNE-30 against Saccharomyces cerevisiae and Rhizopus stolonifera were 35.56 mm and 37.59 mm, respectively, while EuNE-5 induced zones of inhibition against the same fungi were 28.95 mm and 29.71 mm, respectively. A similar fungal inhibition pattern was observed by Basumatary, Kalita, et al, 2022 , Basumatary, Mukherjee, et al, 2022 with isolated fungi ( Basumatary, Mukherjee, et al, 2022 ) and Li, Zhao, Li, & Zhou, 2021 against Penicillium Italicum when exposed to eugenol nanoemulsions ( Li et al, 2021 ).
Fig.
…”
Section: Resultssupporting
confidence: 74%
“…The diameter of the zones of inhibition of EuNE-30 against Saccharomyces cerevisiae and Rhizopus stolonifera were 35.56 mm and 37.59 mm, respectively, while EuNE-5 induced zones of inhibition against the same fungi were 28.95 mm and 29.71 mm, respectively. A similar fungal inhibition pattern was observed by Basumatary, Kalita, et al, 2022 , Basumatary, Mukherjee, et al, 2022 with isolated fungi ( Basumatary, Mukherjee, et al, 2022 ) and Li, Zhao, Li, & Zhou, 2021 against Penicillium Italicum when exposed to eugenol nanoemulsions ( Li et al, 2021 ).
Fig.
…”
Section: Resultssupporting
confidence: 74%
“…The mean particle size of the Pickering emulsion added to Eu was 296.0 ± 11.2 nm, the PDI value was 0.457 ± 0.039, and the absolute value of zeta potential was 20.1 ± 0.9 mV. In a study, Li et al prepared an Eu nanoemulsion containing limonin (an antimicrobial component from citrus seeds), which showed that the mean particle size of Eu nanoemulsions was 213.7 nm, and presented a larger particle size of 245.7 nm with the addition of limonin [25]. In another study, a sub-micron injectable emulsion of Eu was developed with an average particle size of 176.1 ± 10.3 nm and a potential of −40.2 ± 1.8 mV, which showed excellent stability and safety compared to Eu solutions [26].…”
Section: Analysis Of Emulsionmentioning
confidence: 99%
“…Concerning antifungal and protection properties of nanoformulations of phytochemicals, eugenol (4-allyl-2-methoxyphenol) and limonin were formulated into a nanoemulsion and showed high inhibition against blue mold caused by P. italicum in citrus fruits [6]. Cinnamaldehyde, eugenol and carvacrol nanoemulsions strongly inhibited P. digitatum and were applied to the postharvest preservation of citrus fruit [21].…”
Section: In Vivo Efficacy Of Turmeric Nanoparticles Against Anthracno...mentioning
confidence: 99%